Multidisciplinary Team Meeting Proposal and Final Therapeutic Choice in Early Breast Cancer: Is There an Agreement? - Bortot, Lucia; Targato, Giada; Noto, Claudia; Giavarra, Marco; Palmero, Lorenza; Zara, Diego; Bertoli, Elisa; Dri, Arianna; Andreetta, Claudia; Pascoletti, Gaetano; Poletto, Elena; Russo, Stefania; et al. (Frontiers in Oncology, 2022)
A multidisciplinary team meetings (MDMs) approach in breast cancer (BC) management is a standard of care. One of the roles of MDMs is to identify the best diagnostic and therapeutic strategies for patients (pts) with new diagnosis of early BC. The purpose of this study was to define whether there was agreement between what decided during the MDMs and what actually applied. In addition, the study explored factors associated with discordance. We conducted a retrospective study of a consecutive series of 291 pts with new diagnosis of early BC, discussed at MDMs at the University Hospital of Udine (Italy), from January 2017 to June 2018. The association between clinico-biological factors and discordance was explored through uni- and multi-variate logistic regression analysis. Median age was 62 years (range 27-88 years). Among invasive early BC patients, the most frequent phenotype was luminalA (38%), followed by luminalB (33%), HER2-positive (12%) and triple negative (5%). In situ carcinoma (DCIS) represented 12% of cases. Median time from MDMs discussion to first oncologic examination was 2 weeks. Rate of discordance between MDMs-based decision and final choice, was 15.8% (46/291). The most frequent reason for changing the MDMs-based program was clinical decision (87%). Follow-up was preferred to the chemotherapy (CT) proposed within the MDMs in 15% of cases, and to the endocrine therapy (ET) in 39% of cases (among these, 44.5% had diagnosis of DCIS). Therapeutic change from sequential CT-ET to ET alone was chosen in 16/46 pts (35%): among these pts, 7 had a luminalB disease and 6 had a HER2-positive disease. On univariate analysis, factors associated with discordance were values of Ki-67 14-30% (OR3.91; 95%CI 1.19-12.9), age>70 years (OR2.44, 95%CI 1.28-4.63), housewife/retired status (OR2.35, 95%CI 1.14-4.85), polypharmacy (OR1.95; 95%CI 1.02-3.72), postmenopausal status (OR4.15; 95%CI 1.58-10.9), high Charlson Comorbidity Index (OR 1.31; 95%CI 1.09-1.57). Association with marital status, educational level, alcool and smoke habits, presence of caregiver, parity, grading, histotype and phenotype, stage was not statistically significant. On multivariate analysis, only ki-67 value maintained its statistical significance. Our study could be useful for enhancing the role of MDMs in clinical decision-making process in early BC.